Low-Density Lipoprotein Induced Expression of Connective Tissue Growth Factor via Transactivation of Sphingosine 1-Phosphate Receptors in Mesangial Cells - El-Shewy, Hesham M. (Endocrine Society, 2012)
The pro-fibrotic connective tissue growth factor (CTGF) has been linked to the development and progression of diabetic vascular and renal disease. We recently reported that low-density lipoproteins (LDL) induced expression of CTGF in aortic endothelial cells. However, the molecular mechanisms are not fully defined. Here, we have studied the mechanism by which LDL regulates CTGF expression in renal mesangial cells. In these cells, treatment with pertussis toxin abolished LDL-stimulated activation of ERK1/2 and c-Jun N-terminal kinase (JNK), indicating the involvement of heterotrimeric G proteins in LDL signaling. Treatment with LDL promoted activation and translocation of endogenous sphingosine kinase 1 (SK1) from the cytosol to the plasma membrane concomitant with production of sphingosine-1-phosphate (S1P). Pretreating cells with SK inhibitor, dimethylsphinogsine or down-regulation of SK1 and SK2 revealed that LDL-dependent activation of ERK1/2 and JNK is mediated by SK1. Using a green fluorescent protein-tagged S1P(1) receptor as a biological sensor for the generation of physiologically relevant S1P levels, we found that LDL induced S1P receptor activation. Pretreating cells with S1P(1)/S1P(3) receptor antagonist VPC23019 significantly inhibited activation of ERK1/2 and JNK by LDL, suggesting that LDL elicits G protein-dependent activation of ERK1/2 and JNK by stimulating SK1-dependent transactivation of S1P receptors. Furthermore, S1P stimulation induced expression of CTGF in a dose-dependent manner that was markedly inhibited by blocking the ERK1/2 and JNK signaling pathways. LDL-induced CTGF expression was pertussis toxin sensitive and inhibited by dimethylsphinogsine down-regulation of SK1 and VPC23019 treatment. Our data suggest that SK1-dependent S1P receptor transactivation is upstream of ERK1/2 and JNK and that all three steps are required for LDL-regulated expression of CTGF in mesangial cells.